A COMPARATIVE EFFICACY BETWEEN STRENGTH AND STABILISATION TRAINING PROGRAMMES IN THE IMPROVEMENT OF TRUNK AND HIP MUSCLES ACTIVATIONS OF HEALTHY FEMALES SUBJECT: AN IMPLICATION FOR THE REHABILITATION PRACTITIONERS: Life Science -Physiology - GASIBAT, QAIS; SIMBAK, NORDIN; ABD AZIZ, ANIZA; MUAZU MUSA, RABIU (International Journal of Life Science and Pharma Research, 2017)
Physical therapists use a variety of training when rehabilitating patients with low back pain (LBP). The traininganalysed are often used in rehabilitation programmes for the spine, hip, and knee. Evidence has demonstrated that the prevalence of lower back pain (LBP) among women population is alarmingly higher due to the hormonal and reproductive factors such as irregular or prolonged menstrual cycle and hysterectomy. As a result, appropriate selection and designation of a training programme capable of stimulating the trunkand hip muscles could be beneficial in both rehabilitation and prevention of LBP. The current study compared the effectiveness of strength training programme (STTP) with stabilisation training programme (SBTP) intending to ascertaining the most effective in stimulating the muscles activations.50 healthy females with normal BMI and ages range from 19 to 24 years randomly allotted to STTP, and SBTP underwent five different sets of exercises three times a week for five weeks. Electromyography (EMG) data were collected from 5 muscles of rectus abdominis, external oblique, multifidus, gluteus maximus and gluteus medius. The readings from the EMG were compared after the five weeks interventions. An independent t-test was used to examine the comparative efficacy between the STTP and SBTP on the targeted muscles. A statistically significant difference of the muscle activations between the two compared training modalitieswas obtained p < 0.05. The SBTP intervention is shown to be more efficient in stimulating the females’ pelvic muscles activations as opposed to STTP. SBTP could, therefore, be a practical measure for prevention and rehabilitation of LBP.